2020
DOI: 10.3758/s13415-020-00839-9
|View full text |Cite
|
Sign up to set email alerts
|

I am happy for us: Neural processing of vicarious joy when winning for parents versus strangers

Abstract: This study investigated the neural processes underlying vicarious joy and their dependence on emotional closeness. Prior studies revealed that the nucleus accumbens (NAcc) is a target brain region for processing rewards for self, but the neural mechanisms of processing rewards for others are not yet well understood. A functional magnetic resonance imaging (fMRI) paradigm was employed in young adults (N = 30), in combination with a self-report questionnaire on the perceived emotional closeness to the target. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 71 publications
4
12
0
Order By: Relevance
“…First, prosocial learning was restricted to unknown others and should be extended in future research to other beneficiaries. Previous studies have shown that prosocial behaviors and their neural correlates in adolescence strongly depend on the beneficiary (e.g., (Brandner et al, 2020;Schreuders et al, 2018;Westhoff et al, 2020). Whether such differences between beneficiaries are also visible in prosocial learning and the concurrent neural tracking of PEs, is an interesting question for future studies.…”
Section: Discussionmentioning
confidence: 94%
“…First, prosocial learning was restricted to unknown others and should be extended in future research to other beneficiaries. Previous studies have shown that prosocial behaviors and their neural correlates in adolescence strongly depend on the beneficiary (e.g., (Brandner et al, 2020;Schreuders et al, 2018;Westhoff et al, 2020). Whether such differences between beneficiaries are also visible in prosocial learning and the concurrent neural tracking of PEs, is an interesting question for future studies.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, a prior study found similar activation patterns for a close friend receiving a reward compared with a personal reward but no vicarious reward response was observed when a stranger received a reward ( Braams et al, 2014 ). In a recent study in adults, we have also shown that in the NAcc vicarious reward activation for parents is more similar to personal reward responses compared to vicarious reward activation for strangers ( Brandner et al, 2020 ).…”
Section: Introductionmentioning
confidence: 62%
“…In this study, we investigated the relationship between neural vicarious reward processing and cooperative behavior for family members and strangers across adolescence. Vicarious reward responses were measured through self-reports of pleasure from winning for others and NAcc responses during a false-choice fMRI task ( Brandner et al, 2020 ) that was played with three targets: mothers, fathers, and strangers. These vicarious reward measures were related to cooperative behavior assessed by the prisoner’s dilemma (PDG) and social dilemma (SDG) games.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations